A Case of De Novo CD5+ Disseminated Intravascular Large B-Cell Lymphoma Presenting as Multiorgan Failure. (29th September 2016) - Singh, Daulath; Kapuria, Devika; Nanua, Suparna; Gaur, Rakesh
Abstract : Intravascular large B-cell lymphoma is an extremely rare extranodal lymphoma that proliferates in the lumen of the blood vessels while sparing the organ parenchyma. It usually presents with CNS and skin involvement. A 65-year-old Caucasian female presented with fevers and chills of 3-4 months' duration. Bone marrow biopsy done 3 months prior showed no significant myelodysplasia or lymphoid aggregates. The patient later died due to multiorgan failure. A bone marrow biopsy showed 20–30% CD5+ B cells consistent with infiltrative large B-cell lymphoma. An autopsy performed revealed diffuse intravascular invasion by lymphoma cells. Multiorgan involvement by intravascular B-cell lymphoma is very rare. Based on our literature review and to the best of our knowledge, there are only 5 case reports describing the presentation of this lymphoma with multiorgan failure. The immunophenotypic studies performed revealed that our patient had de novo CD5+ intravascular large B-cell lymphoma which is known to be aggressive with very poor prognosis. Although it is an extremely rare lymphoma, it should be considered as a potential cause of multiorgan failure when no other cause has been identified. A prompt tissue diagnosis and high-dose chemotherapy followed by ASCT can sometimes achieve remission.